2020
DOI: 10.3390/mi11080733
|View full text |Cite
|
Sign up to set email alerts
|

Micromachining of Invar Foils with GHz, MHz and kHz Femtosecond Burst Modes

Abstract: In this work, a burst mode laser is used for micromachining of 20 µm–250 µm thick Invar (Fe64/Ni36) foils. Holes were drilled by firing multiple pulses transversely onto the sample without moving the beam (percussion drilling). The utilized laser system generates a burst of a controllable number of pulses (at 1030 nm) with tunable pulse-to-pulse time spacing ranging from 200 ps to 16 ns. The sub-pulses within the burst have equal amplitudes and a constant duration of 300 fs that do not change regardless of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…It has been reported by several groups that both the ablated volume per time and the energy specific volume can be increased by several factors when processing material with ultra-short burst pulses with intra-burst repetition rates in the GHz regime compared to single pulse operation. For the milling of copper, it was reported that the maximum energy specific volume can increase by a factor of three [ 135 ], whereas for steel it can increase by a factor of two when using GHz burst pulses instead of single pulses [ 112 , 135 , 137 ]. For the drilling of copper, it was reported that the maximum energy specific volume can increase by a factor of 3.5; for steel, it can increase by a factor of 4.6; and, for aluminum, it can increase by a factor of 5.8 when using GHz burst pulses instead of single pulses [ 136 ].…”
Section: Physics Of Ultra-short Burst Pulse Ablation Of Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported by several groups that both the ablated volume per time and the energy specific volume can be increased by several factors when processing material with ultra-short burst pulses with intra-burst repetition rates in the GHz regime compared to single pulse operation. For the milling of copper, it was reported that the maximum energy specific volume can increase by a factor of three [ 135 ], whereas for steel it can increase by a factor of two when using GHz burst pulses instead of single pulses [ 112 , 135 , 137 ]. For the drilling of copper, it was reported that the maximum energy specific volume can increase by a factor of 3.5; for steel, it can increase by a factor of 4.6; and, for aluminum, it can increase by a factor of 5.8 when using GHz burst pulses instead of single pulses [ 136 ].…”
Section: Physics Of Ultra-short Burst Pulse Ablation Of Metalsmentioning
confidence: 99%
“…A study about laser drilling of invar with ultra-short MHz and GHz bursts has shown an ambiguous picture. Depending on the sample thickness and intra-burst delay, slightly shorter drilling durations or even longer drilling durations were reported compared to drilling without bursts [ 137 ].…”
Section: Applications Using Burst Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used bursts of femtosecond pulses where the sub-pulses had a temporal separation of 400 ps. From previous investigations [ 21 ] it was known, that the heat input on the surface would be much more pronounced in this time scale as compared to a larger temporal separation (nanoseconds) setting. However, it was unknown what the best parameter combination that produces the highest heat flux onto the surface is.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was seen that implants with higher surface roughness values increase the risk of post–surgical complications (e.g., posterior capsular opacification) that lead to decrease in vision [ 15 ]. Recently it was discovered that using bursts of femtosecond laser pulses, when each pulse is divided into a sequence of sub-pulses with a temporal separation of few tens of nanoseconds or hundreds picoseconds, improves laser material processing by boosting the ablation efficiency [ 16 , 17 , 18 , 19 , 20 , 21 ]. It was also demonstrated, that by using bursts of pulses it is possible to further decrease the surface roughness compared to using the conventional single femtosecond pulse regimes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%